2018
DOI: 10.1080/10715762.2018.1459043
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length is independently associated with age, oxidative biomarkers, and sport training in skeletal muscle of healthy adult males

Abstract: In skeletal muscle, which mainly contains postmitotic myonuclei, it has been suggested that telomere length remains roughly constant throughout adult life, or shortens in response to physiopathological conditions in muscle diseases or in the elderly. However, telomere length results from both the replicative history of a specific tissue and the exposure to environmental, DNA damage-related factors, therefore the predictive biological significance of telomere measures should combine the analysis of the various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 62 publications
0
22
0
4
Order By: Relevance
“…This relatively small sample size is due to the difficulty to recruit older adults for an invasive study with a muscle biopsy. Telomere length is highly variable between individuals and is impacted by multiple genetic, epigenetic and environmental factors [10,11,54,55]. While we cannot fully account for all these factors, a strength of this study is that our cohort is very homogeneous with regards to confounding factors that can impact TL (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relatively small sample size is due to the difficulty to recruit older adults for an invasive study with a muscle biopsy. Telomere length is highly variable between individuals and is impacted by multiple genetic, epigenetic and environmental factors [10,11,54,55]. While we cannot fully account for all these factors, a strength of this study is that our cohort is very homogeneous with regards to confounding factors that can impact TL (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The length of telomeres varies considerably between individuals of the same chronological age and is therefore indicative of biological age [8]. The inter-individual variability in TL is thought to be influenced by genetics, epigenetics and environ-mental factors including oxidative stress, and inflammation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Rae et al ( 46 ) demonstrated that athletes and sedentary individuals presented similar telomere lengths in the cells of the musculoskeletal system. Magi et al ( 47 ) demonstrated that skeletal muscles from healthy adults display an age-dependent telomere attrition rate, which is partially influenced by exercise. In turn, studies that evaluate telomere lengths in immune-related cells are also conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of modern concepts, the role of oxidative stress becomes more and more clear, that is the imbalance between prooxidants and antioxidant defense mechanisms of a body as the core source of pathogenesis of numerous acute and chronic conditions and diseases, such as atherosclerosis, diabetes mellitus, ischemia, etc. [3,4].…”
mentioning
confidence: 99%
“…In this case, both cellular (defects in mitochondrial respiration and specific enzymes) and exogenous mechanisms can participate. Ultimately, all these effects can lead to tension and subsequent decompensation of the mechanisms of antioxidant defense of a body and the development of oxidative stress that manifests itself at cellular, tissue and organ levels [3,4].…”
mentioning
confidence: 99%